Antiretroviral Therapy Use and HIV Transmission Among Discordant Couples in Nonresearch Settings in Kigali, Rwanda. Issue 6 (11th June 2021) - Nyombayire, Julien; Ingabire, Rosine; Mukamuyango, Jeannine; Karita, Etienne; Mazzei, Amelia; Wall, Kristin M.; Parker, Rachel; Tichacek, Amanda; Allen, Susan; Hunter, Eric; Price, Matt A.
Abstract : Couples in a routine government clinic couples' HIV testing and follow-up program in Rwanda had an 89% reduction in HIV incidence when index partners were using antiretroviral treatment. Supplemental digital content is available in the text. Abstract : Background: Antiretroviral therapy (ART) efficacy for HIV prevention among discordant couples has been demonstrated in clinical trials. Effectiveness outside of research settings is less well understood. Methods: HIV-discordant couples were enrolled in couples' testing and follow-up at 20 government clinics in Kigali from 2010 to 2014. We performed viral linkage analysis on seroconverting couples to determine infection sources (intracouple vs. extracouple). Antiretroviral therapy use in index partners was collected at baseline and during follow-up by self-report with verification of government medical records. Results: A total of 3777 HIV-discordant couples were identified and followed up at government health clinics. Fifty-four incident HIV infections were identified, of which 36 were confirmed linked to the index partner, 4 were unlinked, and 14 were unknown. Among the 50 linked or unknown transmission pairs, 38% occurred among couples in which the index partner was on ART (HIV incidence rate of 0.63/100 person-years), whereas 62% occurred among couples in which the index partner was not on ART (HIV incidence rate of 5.51/100 person-years; adjusted rate ratio, 6.9). HIV acquisition was higher in women than in men with non-ART using index partners ( P < 0.001). Conclusions: Couples in a government clinic couples' HIV testing and follow-up program in Rwanda had an 89% reduction in HIV incidence when index partners were using ART, slightly lower than efficacy estimates from randomized trials. Antiretroviral therapy for prevention should be prioritized for key populations including discordant couples identified via couples' voluntary counseling and testing, with increased efforts to improve uptake, adherence, and viral load monitoring.